2022
DOI: 10.1101/2022.03.26.485076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The clinically relevant MTARC1 p.Ala165Thr variant impacts neither the fold nor active site architecture of the human mARC1 protein

Abstract: Recent genome-wide association studies (GWAS) have shown a common variant of the mARC1 protein to be associated with liver disease. Herein, we present the crystal structure of this mARC1 p.Ala165Thr at near-atomic resolution. No relevant differences between the structure of wild type mARC1 and the variant protein are detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The structure has the PDB accession code 7P41, and experimental details are also publicly available. [ 5 ] Briefly, while the electron density of the mutated residue is well‐defined, no other alterations of the structure are observed: The alpha helix predicted to be lost in the variant is fully intact, as is the molybdopterin cofactor and the molybdenum ion's coordination environment (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
“…The structure has the PDB accession code 7P41, and experimental details are also publicly available. [ 5 ] Briefly, while the electron density of the mutated residue is well‐defined, no other alterations of the structure are observed: The alpha helix predicted to be lost in the variant is fully intact, as is the molybdopterin cofactor and the molybdenum ion's coordination environment (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
“…Previous studies indicated that the protective loss-of-function MTARC1 variants identified by genetics do not affect enzymatic activity or protein folding. 18 19 We reasoned that the protective effect of these variants must be mediated by some other mechanism such as protein stability or subcellular localization. Consequently, we studied the localization and protein accumulation of 3 published human missense and nonsense variants associated with protection from MASH (A allele of rs2642438, p.M187K, and p.R200*), 11 as well as one synthetic mutation known to abrogate the enzymatic function of the protein, p.C273A 20 using in vitro overexpression experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from mARC1 crystal structures and published data showing similar molybdenum content among different recombinant mARC1 variants both demonstrate that residue 165 is not involved in Moco-binding (30,39). A recent crystal structure study of mARC1 A165T showed that there were alternate conformations of Thr165, even though no difference in protein folding and thermal stability was found between A165T and WT (40).…”
Section: Discussionmentioning
confidence: 99%